Does weight status affect academic performance? Evidence from Australian children. Issue 29 (21st June 2018) - Shi, Hui; Li, Chuhui
ABSTRACT: This article investigates the impact of children's weight status on their academic performance using the Longitudinal Survey of Australian Children. Considering the endogeneity of the weight status variable (obesity or overweight), to obtain consistent estimates of its impact, we use the body mass index of biological parents as instrumental variables. The two-stage least square estimation shows that obesity or overweight has a significant negative impact on academic performance. Furthermore, the effect of child weight status is different across grade levels. Overweight has a larger negative impact on academic performance for senior year students, especially on numeracy.